Identification Prevalence Of Endoparasite In Canines Bayan Lepas, Penang - Rekasni Adallin A/P Morgan A/P Morgan; Setiawan Koesdarto; Maslichah Mafruchati; Mufasirin; Adiana Mutamsari Witaningrum (Journal of Parasite Science (JoPS), 2023)
This study aims to determine the type, prevalence and influence of sex and age on the prevalence of gastrointestinal parasites on dogs in Bayan Lepas, Penang. A total of 100 samples of dog feces were collected from three Districts. Feces examination was performed by direct smear, sedimentation, and floatation methods. The kind of helminth was Trichuris sp. 2% (2/100), Dipylidium sp. 2% (2/100), Ancylostoma sp. 1% (1/100), Toxocara sp. 2% (2/100), Strongyloides sp. 2% (2/100) and protozoa Isospora sp. 18% (18/100), Giardia sp. 1% (1/100) samples were positively infected by helminth and protozoa. According to the statistics analysis, could be concluded that sex and age do not affect the prevalence of gastrointestinal parasite.